Ambidextrous Organizational Culture and Psychological Safety: Encourage Innovative Work Behavior of Higher Education Lecturers in Indonesia - Fatihah, Rezky Nurul; Etikariena, Arum (Jurnal Indonesia Sosial Sains, 2025)
Rapid global change requires organizations, including universities, to innovate in producing new ideas and adapting to a dynamic environment. Lecturer innovation in research, community service, and learning methods is the key to increasing competitiveness and will produce skilled lecturers. Lecturers are crucial in encouraging innovative behavior that supports academic and research progress. This research explores the influence of ambidextrous culture as an environmental factor on lecturers' innovative work behavior, with psychological safety as a mediating variable. This research uses a quantitative approach with a cross-sectional research design. The number of participants in this research was 107 PTN lecturers in Indonesia using a sampling technique, namely convenience sampling. Hypothesis testing using SPSS version 27 software with Hayes' process model 4. The results of the study found that ambidextrous organizational culture has a positive and significant influence on innovative work behavior with results (β = 0.702, p < 0.001), but the mediating role psychological safety does not play a role in the indirect relationship between ambidextrous organizational culture on innovative work behavior and results (β=0.088, p > 0.153) with the confidence interval value (95% CI) (LL=-0.033, UL=0.209) including zero, indicating that this mediation effect is not proven.